PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PUBLIKASI AKTIVITAS PENDIDIKAN DI SMA LAB SCHOOL UNIVERSITAS SYIAH KUALA BANDA ACEH - Nur Shabayani; Tihalimah Tihalimah (STKIP Pesisir Selatan, 2026)
Social media serves several purposes for schools: disseminating information, increasing school-community contact, and building a positive school image. The objectives of this study were to (1) identify the positive influence of social media use on educational activities at SMA Labschool Universitas Syiah Kuala Banda Aceh and (2) assess the process of planning and developing content on social media for these purposes. A qualitative approach using descriptive methodology was used in this study. The Principal, PR staff, and publishing coordinator were all involved in data collection through interviews, observations, and document collection. By comparing multiple sources of information, the data became more valid. The results showed that social media use at SMA Labschool Universitas Syiah Kuala was carried out in a planned manner in accordance with the school's vision and mission. Promotion strategies were carried out by setting upload schedules, selecting platforms according to the audience, and presenting content that has character-building values. The use of social media has had positive impacts such as increasing school awareness and image, increasing parental trust, increasing the number of new students, and increasing student participation and creativity. The results of this study indicate that promoting educational activities through social media requires a well-thought-out strategy, as well as sustainable content management and strong community support for schools.